PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN NON MEDIS PADA RS MELATI Tangerang - Ira Putri; Muhamad Guruh (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the influence of Work Motivation and Work Discipline on Non-Medical Staff at Melati Hospital Tangerang. The research employs a quantitative method, utilizing secondary data in the form of questionnaires distributed to Non-Medical Staff at Melati Hospital Tangerang. The methods used include the Classical Assumption Test techniques, which consist of the Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test. Additionally, the study applies Multiple Linear Regression Analysis, Hypothesis Testing (t-test), Simultaneous Test (F-test), and Coefficient of Determination Test. The variables include Work Motivation (X1), Work Discipline (X2), and Employee Performance (Y). The analysis was conducted using SPSS Version 26 software. The results indicate that Work Motivation (X1) has a positive and significant effect on Employee Performance (Y) among non-medical staff at Melati Hospital Tangerang, with a significance value of 0.000 < 0.05 and a t-value of 4.223 > t-table value of 1.659. Similarly, Work Discipline (X2) has a positive and significant effect on Employee Performance (Y) among non-medical staff at Melati Hospital Tangerang, with a significance value of 0.000 < 0.05 and a t-value of 4.996 > t-table value of 1.659. Both Work Motivation (X1) and Work Discipline (X2) collectively have a positive and significant impact on Employee Performance (Y) among non-medical staff at Melati Hospital Tangerang, with an F-value of 36.629 > F-table value of 3.08 and a significance value of 0.000 < 0.05.